PEMBELAJARAN SENI TARI KUDA LUMPING DI DESA DUKUHWALUH KECAMATAN KEMBARAN KAB. BANYUMAS - Daryanto Daryanto (Khazanah Pendidikan, 2011)
The goals this research were to determine: 1). What are the requirements given to prospective players of Kuda Lumping; 2). What material provided and what methods are used in training Kuda Lumping; 3). What is the cost required to conduct training of Kuda Lumping, and from which source. 4). How long does it take to produce players who are ready to perform Kuda Lumping showcased in front of an audience. From the research result shows that: 1. Requirements given to players of Kuda Lumping (Ebeg), are namely: (1) has Kuda Lumping, (2) can dance in group / compact dance, (3) perform the ritual bathing and diving in rivers and (4) conduct ”Ngasrep” or fasting for 3 (three) days without stopping. 2. The practice material was first given to prospective players Kuda Lumping is dance. In practing the dance material, the new dancers were directly guided by the seniors. The method used is by giving examples of dancing by the senior players to prospective players. When giving examples accompanied by gamelan / music, while dancer candidates of Kuda Lumping followed. 3. Fee required for training activities at least IDR 400,000,- (four hundred thousand rupiah). This cost does not include the cost to buy a kuda lumping. Sources of cost comes from the self-help group members of kuda lumping, like dalang ( director of the dance ) and local people. It means the training and activities of Kuda Lumping, did not receive funding / donations from the government, both the village and district governments. The cost for training activities was used to rent the gamelan, to purchase clothing / costume players, “sesaji”, consumption and honorariums. 4. To train / produce, it take a player at least 3.5 (three and a half) months and a maximum of 7 (seven) months. This calculation is based on the starting time of dance exercise, until doing the bath in the river as the last stage. Key Wordsi: Kuda lumping, learning ,ngasrep, ritual of bathe, ritual offerings, wayang,